Medical Communications in an Agency Setting: A Career Option for Pharmacists. (June 2022) - Miernicki, Samantha; Anagnostos, Gregory; Nathan, Joseph P.; Grossman, Sara
Medical communications (MedComms) agencies serve the varied needs of the pharmaceutical industry and other healthcare-related organizations. These agencies present a unique practice opportunity for pharmacists who possess the requisite knowledge and skillset to flourish and grow professionally in this environment. Published information about this sector of the industry is limited. To this end, this article provides an overview of the MedComms agency setting and describes the services provided by such agencies. These include the development of branded and/or unbranded communications materials in the form of publications, oral and video presentations, slide decks, and other materials. MedComms professionals also facilitate and support professional meetings and presentations, such as congresses, symposia, and advisory boards. Other services that MedComms agencies provide include engaging key opinion leaders, providing clinical trial services, and brand identification or positioning. The article describes the opportunities for pharmacists in this field, key characteristics and skills needed to succeed in this industry, and the pathway for pharmacists to enter this field.